Bank asset and liability management,strategy, trading, analysis - Choudhry, Moorad
Bank asset and liability management : strategy, trading, analysis / Moorad Choudhry .- Singapore : John Wiley & Sons, Inc , 2007 .- xxiii, 1415 p. : ill. ; 24 cm .- 978047082135